Adjustment Costs and Long Run Spatial Agglomerations - William Brock; Anastasios Xepapadeas; Athanasios Yannacopoulos (Fondazione Eni Enrico Mattei (FEEM), 2013)
We introduce knowledge spillovers as an externality in the production function of competitive firms operating in a finite spatial domain under adjustment costs. Spillovers are spatial as productive knowledge flows more easily among firms located nearby. When knowledge spillovers are not internalized by firms spatial agglomerations may emerge endogenously in a competitive equilibrium, however, they do not emerge at the steady state of the social optimum.
Keywords: D21; R3; C61; 330; Investment Theory; Adjustment Costs; Spatial Agglomerations